On the Utilization of Dietary Glycerol in Carnivorous Fish—Part II: Insights Into Lipid Metabolism of Rainbow Trout (Oncorhynchus mykiss) and European Seabass (Dicentrarchus labrax) - Viegas, Ivan; Palma, Mariana; Plagnes-Juan, Elisabeth; Silva, Emanuel; Rito, João; Henriques, Luís F.; Tavares, Ludgero C.; Ozório, Rodrigo O. A.; Panserat, Stéphane; Magnoni, Leonardo J. (Frontiers in Marine Science, 2022)
The final version of the article will be published here soon pending final quality checks.